The Efficacy of Diverse Interventions for Postpartum Blues and Postpartum Depression: A Scoping Review - Hafitasari, Nurisna Ummu (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Postpartum blues is a common condition experienced by mothers after childbirth, and can progress to postpartum depression. Various interventions have been proposed to reduce these symptoms, but their effectiveness varies. Objectives: This review aims to explore the effectiveness of various interventions in reducing symptoms of postpartum blues and postpartum depression. Methods: This study followed a scoping review method based on PRISMA, with literature searches from major databases such as PubMed, ScienceDirect, and Scopus. Articles that met the inclusion criteria from 2020-2024 were analyzed using a descriptive approach. Results: Thirteen studies were identified. Non-pharmacological interventions, including Mindfulness-Based Stress Reduction, app-based Cognitive Behavioral Therapy, and auricular acupressure, demonstrated a significant reduction in postpartum depression symptoms. For instance, a study on auricular acupressure showed a very large effect in reducing postpartum blues symptoms by day 10 after delivery. Physical interventions and social support also showed significant psychological benefits for postpartum mothers. Conclusion: Non-pharmacological interventions, especially technology-based and mindfulness, are effective in reducing symptoms of postpartum blues and postpartum depression. Further research is needed to explore the long-term effects and clinical implementation of these interventions.